Use of Tomato By-Products Encapsulates to Enrich Vegetable-Based Products: A Cucumber Beverage - Laleh Mozafari; Lorena Martínez-Zamora; Francisco Artés-Hernández (Biology and Life Sciences Forum)
Food industries generate tomato by-products rich in health-promoting compounds, which can be extracted and encapsulated for use in food products. This study aimed to fortify cucumber juice with encapsulated tomato by-products rich in carotenoids and assess its shelf life. The encapsulated tomato by-product, prepared by spray-drying with maltodextrin and inulin, was added to cucumber juice (5 g L−1). The total antioxidant capacity (TAC) and microbial load were monitored for 3 weeks at 4 °C. High hydrostatic pressure (HHP) treatment improved the TAC by ~25% and reduced the microbial load by ~69%. No significant sensory or physical changes were observed, suggesting fortification enhances beverage health benefits during refrigeration.